2000
DOI: 10.1177/000331970005101003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Protein Diets on Coronary Blood Flow

Abstract: Recent research has demonstrated that successful simultaneous treatment of multiple risk factors including cholesterol, triglycerides, homocysteine, lipoprotein (a) [Lp(a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…10, 50 Individual studies that combine regular exercise with either unrestricted or energy-restricted low-carbohydrate diets have observed similar weight loss to our intervention at 6 months: 12.0 (95% CI±1.8) kg; 51 and at 1 year: 10.9 (95% CI±1.2) kg, 52 and 12.2 (includes telemonitoring, 95% CI±1.3) kg reductions. 53 However, studies on the effects of low-carbohydrate diets have shown higher rates of all-cause mortality, 54 decreased peripheral flow-mediated dilation, 55 worsening of coronary artery disease, 56 and increased rates of constipation, headache, halitosis, muscle cramps, general weakness and rash. 10 Other energy-restricted diets can be effective for weight loss, for example, one study using a 1 500 kcal daily intake, with 50% carbohydrate, 30% fat and 20% protein achieved an average 17.3 (95% CI±1.6) kg reduction in weight at 36 weeks, which is significantly more than our results.…”
Section: Discussionmentioning
confidence: 99%
“…10, 50 Individual studies that combine regular exercise with either unrestricted or energy-restricted low-carbohydrate diets have observed similar weight loss to our intervention at 6 months: 12.0 (95% CI±1.8) kg; 51 and at 1 year: 10.9 (95% CI±1.2) kg, 52 and 12.2 (includes telemonitoring, 95% CI±1.3) kg reductions. 53 However, studies on the effects of low-carbohydrate diets have shown higher rates of all-cause mortality, 54 decreased peripheral flow-mediated dilation, 55 worsening of coronary artery disease, 56 and increased rates of constipation, headache, halitosis, muscle cramps, general weakness and rash. 10 Other energy-restricted diets can be effective for weight loss, for example, one study using a 1 500 kcal daily intake, with 50% carbohydrate, 30% fat and 20% protein achieved an average 17.3 (95% CI±1.6) kg reduction in weight at 36 weeks, which is significantly more than our results.…”
Section: Discussionmentioning
confidence: 99%
“…Could it be that whole food, plant-based diets that have successfully demonstrated the regression of CAD in response to markedly lower lipid values, including HDL, may have facilitated the conversion of HDL from a proinflammatory to an anti-inflammatory, atheroprotective particle [2325]? And could it be that these properties are more important than the absolute HDL numbers [26, 27]?…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms and abnormalities on the laboratory tests resolved after the high protein intake was discontinued [27]. In a case-control study, subjects (treatment group/TG) were studied for 1 year by using myocardial perfusion imaging (MPI), echocardiography (ECHO), and serial blood work [28]. MPI and ECHO were performed at the beginning and end of the study for each individual.…”
Section: Increased Cancer Risk Disorders Of Liver Function and Pmentioning
confidence: 99%
“…The TG group studied modified their dietary intake as instructed. Additional subjects (high protein group/HPG) elected a different dietary regimen consisting of a “high-protein” diet [28]. Subjects in the TG demonstrated a reduction in each of the independent variables studied with regression in both the extent and severity of coronary artery disease (CAD) as quantitatively measured by MPI.…”
Section: Increased Cancer Risk Disorders Of Liver Function and Pmentioning
confidence: 99%
See 1 more Smart Citation